Controlling pathogenic risks of water treatment biotechnologies at the source by genetic editing means. (27th November 2021) - Wu, Jie; Liu, Dong‐Feng; Li, Hui‐Hui; Min, Di; Liu, Jia‐Qi; Xu, Peng; Li, Wen‐Wei; Yu, Han‐Qing; Zhu, Yong‐Guan
Summary: Antimicrobial‐resistant pathogens in the environment and wastewater treatment systems, many of which are also important pollutant degraders and are difficult to control by traditional disinfection approaches, have become an unprecedented treat to ecological security and human health. Here, we propose the adoption of genetic editing techniques as a highly targeted, efficient and simple tool to control the risks of environmental pathogens at the source. An 'all‐in‐one' plasmid system was constructed in Aeromonas hydrophila to accurately identify and selectively inactivate multiple key virulence factor genes and antibiotic resistance genes via base editing, enabling significantly suppressed bacterial virulence and resistance without impairing their normal phenotype and pollutant‐degradation functions. Its safe application for bioaugmented treatment of synthetic textile wastewater was also demonstrated. This genetic‐editing technique may offer a promising solution to control the health risks of environmental microorganisms via targeted gene inactivation, thereby facilitating safer application of water treatment biotechnologies.